ANALISIS KANDUNGAN BORAKS PADA BAKSO YANG DIJUAL DI ANDUONOHU KOTA KENDARI SULAWESI TENGGARA - Satya Darmayani; Narti Nasir; Sitti Rachmi Misbah (Jurnal Kesehatan Manarang, 2017)
Fast food consumption today has become a habit of eating for the people in Indonesia. One of the popular fast food is meatballs, but nowadays often found the use of non-food additives in the meatballs, namely borax. The Indonesian Republic Food and Drug Administration has detected the abusive use of borax on food derived from various regions of Indonesia. Borax is a chemical compound derived from heavy metals, namely Boron and commonly used as an anti-fungal and wood preservative. This study aimed to determine the content of borax on meatballs that was sold in Anduonohu, Kendari City of Southeast Sulawesi. Type of research using total sampling conducted by observational descriptive by the qualitative method that was using the method of centrifugation and dry ash processing. The results showed that from 24 samples of meatballs located in Anduonohu, Kendari City, it was proven that none of the meatballs contained borax which could endanger the consumer's health which was marked by no change of green color when heated on the flame. Based on the results of the analysis can be concluded that all sellers of meatballs located in Anduonohu, Kendari City have the knowledge and good attitude. Knowledge and attitude level is one important factor in order to avoid pollution of toxin material. Meatball processing method in Anduonohu, Kendari City has fulfilled the requirement of Indonesian Republic Health Minister Regulation in 2015, Number: 722/Menkes/Per /IX/2015 about food, so people do not have to worry about consuming meatballs located in Anduonohu, Kendari City.